Constructivism-based pathways: Revolutionizing EFL writing instruction for adult learners - Fitrianingsih, Ihtiara (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
In the ongoing pursuit of continuous pedagogical improvement, eclectic teachers find themselves inundated with a multitude of engaging approaches, methods, and techniques. The selection of these should ideally be based on informed pedagogy, with due consideration given to the particular needs of the learners. Through reflective self-inquiry , this paper aims to reveal how a thoughtful teacher reflects on her everyday teaching practices in order to transform them into a more constructivist model of instruction by the stages of initiation, focus on the self, data collection, taking accountability, iterative reflection, and information generation. A description is provided of how the EFL writing classes taught by the author at Universitas Negeri Yogyakarta were managed. This is then confronted with some literature about andragogy and constructivist learning, providing a proposed model for improving future constructivist-based EFL writing instruction for adult learners. The constructivist approach to EFL writing proposed involves several key steps, from conditioning, collaborative inquiry, engaging feedback, work display, to reflective exam, all of which become comprehensive stages within one semester learning in writing courses.